Re-created Selves: Longitudinal Case Studies of Meaning-Making by Women in Retirement - Vivian Wilson Mott Ph.D. (Adult Education Research Conference, 1999)
The purpose of this second phase of longitudinal research was to continue exploration of women's retirement as a mid and late-life developmental transition, particularly looking at the ways in which the ongoing reflection and learning continued to impact the retirement experience of six women.